Novel RCBTB1 variants causing later-onset non-syndromic retinal dystrophy with macular chorioretinal atrophy. (4th May 2022) - Catomeris, Andrew J.; Ballios, Brian G.; Sangermano, Riccardo; Wagner, Naomi E.; Comander, Jason I.; Pierce, Eric A.; Place, Emily M.; Bujakowska, Kinga M.; Huckfeldt, Rachel M.
ABSTRACT: Background: Variants in RCBTB1 were recently described to cause a retinal dystrophy with only eight families described to date and a predominant phenotype of macular atrophy and peripheral reticular degeneration. Here, we further evaluate the genotypic and phenotypic characteristics of biallelic RCBTB1 -associated retinal dystrophy in a North American clinic population. Methods: A retrospective analysis of genetic and clinical features was performed in individuals with biallelic variants in RCBTB1 . Results: Three unrelated individuals of French-Canadian descent with rare biallelic RCBTB1 variants were identified. All individuals shared a novel p.(Ser342Leu) missense variant; one patient was homozygous whereas the other two each possessed a second unique novel variant p.(Gln120*) and p.(Pro224Leu). All three had macula-predominant disease with symptom onset in the fifth decade of life. Conclusion: This report adds to the genetic diversity of RCBTB1 -associated disease. These cases confirm the later-onset, relative to many other retinal dystrophies, and macular focus of disease described in most cases to-date. They are thus a reminder of considering hereditary disease in the differential for later-onset macular atrophy.